Levels of the Tropospheric Ozone in Vitoria/Espírito Santo, Brazil - Silva, Lindalva Marques da (2023)
The aim of this work was to verify ozone concentrations detected in 2004 in the area known as Enseada do Suá. The neighborhood is characterized by heavy traffic on its main road, a major route leading to downtown Vitória and to several other districts of the city, as well as other municipalities in the metropolitan area of Vitória. The ozone detected in the air of Enseada do Suá, 2004, showed that the daily values did not exceed the standards required by Resolution CONAMA nº 03/90, remaining at 160 gm-3, below the established limit.